Labour market effects of retraining for the unemployed- the role of occupations - Julia Lang; Thomas Kruppe (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We analyse the impact of retraining for the unemployed on future labour market success, and estimate effects separately for different target occupations. We use German registry data and apply statistical matching methods. The results show that on average, after a period with strong lock-in effects, retraining increases the employment probability of women by more than 20 percentage points. Effects for male participants are somewhat weaker. Although we find differences in the effectiveness of retraining by target occupations, these differences cannot completely explain the observed gender differences. Healthcare occupations, which are the most frequent target occupations especially of female participants, are among those with the strongest effects. Despite differences between occupational fields, retraining in most of the considered occupations positively affects employment prospects of participants.
Keywords: J24; J68; C14; 330